PERILAKU MAHASISWA DALAM TEMU KEMBALI INFORMASI DI PERPUSTAKAAN STMIK PONTIANAK - Kapitan, Markus; Hanum, Atiqa Nur Latifa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractSearch behavior that is shown by someone when interacting with information systems so that information seeking behavior to meet their needs. Information seeking behavior begins when someone feels that there is knowledge they have when it is less than the knowledge they need. The purpose of this research is to describe students 'behavior in information retrieval at the STMIK library in Pontianak and to describe the students' constraints in information retrieval at the STMIK Library in Pontianak. This research is a field research (empirical). In this study, the type of research used is descriptive research using a qualitative approach. While the data collection method used is observation, interviews, and documentation. In this study, informants were STMIK Pontianak students. The results show that the user does not follow the search phase in accordance with Ellis's theory. Some students search directly into the bookshelf according to their needs, for some reason they already know where they want books. The problem faced by users is the absence of an information search tool.Â Keywords: information seeking behavior, information retrieval